2021
DOI: 10.37077/25200860.2021.34.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth for Cultivated Common carp, Cyprinus carpio Larvae between Earthen Ponds and Recirculation Aquaculture System

Abstract: A comparison was conducted for growth criteria of common carp, Cyprinus carpio larvae cultivated in earthen ponds and recirculation aquaculture system (RAS) depending on live foods (phytoplankton and zooplankton stimulated by buffalo fertilizers in earthen ponds, while the larvae cultivated in RAS were feed on Artemia larvae reproduced in vitro, in addition to manufactured pellets (38% crude protein) for common carp in both systems. Three 2500 m2 earthen ponds were cultivated for 90 days with larvae of initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…For example, Jelkic et al (2012) found that Cyprinus carpio larvae reared at a stocking density of 200 larvae/L in RAS exhibited better survival and growth performance compared to those reared in a mudfish pond (800 000 larvae/ha). However, Mojer, Taher, and Al-Tameemi (2021) have recently shown that earthen ponds resulted in better growth performance of Cyprinus carpio compared to those reared in RAS. The discrepancy in results could be attributed to differences in initial weight with the latter having 0.002 g which resulted in reduced feed intake.…”
Section: Concept Of Recirculating Aquaculture System (Ras)mentioning
confidence: 97%
“…For example, Jelkic et al (2012) found that Cyprinus carpio larvae reared at a stocking density of 200 larvae/L in RAS exhibited better survival and growth performance compared to those reared in a mudfish pond (800 000 larvae/ha). However, Mojer, Taher, and Al-Tameemi (2021) have recently shown that earthen ponds resulted in better growth performance of Cyprinus carpio compared to those reared in RAS. The discrepancy in results could be attributed to differences in initial weight with the latter having 0.002 g which resulted in reduced feed intake.…”
Section: Concept Of Recirculating Aquaculture System (Ras)mentioning
confidence: 97%
“…-the use of high density of carp planting, which far exceeds the capacity of the reservoir to provide aliens with natural food (Martseniuk, 2017;Mojer et al, 2021); -intensive feeding of carp with artificial feed mixtures;…”
Section: Intensive Technologymentioning
confidence: 99%